(untitled) (Iranian Journal of Kidney Diseases, 2014)
Organ transplantation as an undeniable life-saving therapeutic modality fundamentally requires infrastructure, devoted and trained professionals, and positive public attitude to be set up in a well-organized manner at the national level. In addition to sharing achievements and reviewing the increasing trend of transplanted organs in the past 12 years following legislations in Iran, this report raises some concerns from the point of transplantation outcome view.